PENGARUH INFLASI, SUKU BUNGA DAN NILAI TUKAR TERHADAP KINERJA PASAR MODAL INDONESIA - Aldo Arsito; Siagian, Harlyn L.; Pangaribuan, Hisar (JURNAL EKBIS, 2024)
This research aims to contribute to the understanding of the relationship between inflation, interest rates, and exchange rates with the performance of the Indonesian stock market. The research design is an explanatory quantitative study with the objective of determining the influence of interest rates, inflation, and exchange rates on stock market performance. The research sample includes 132 time series data on stock market performance, interest rates, inflation, and the exchange rate of the Rupiah from 2013 to 2023. Sampling was done using a saturated sampling method, resulting in a total of 132 samples. Data analysis was conducted using multiple linear regression analysis with the Statistical Program for Social Sciences (SPSS) 20. The results indicate that inflation, interest rates, and the Rupiah exchange rate simultaneously have a significant impact on stock market performance, with a determination coefficient of 0.442, indicating that 44.2% of the variability in stock market performance can be explained by these three factors. Partially, inflation does not have a significant impact on stock market performance, interestl rates havel a significantl negative impact on stockl market performance, while thel Rupiah exchangel rate hasl a significant positive impact.